Misi di Tengah Krisis Multidimensi - Bobby Kurnia Putrawan; Ramot Peter (Jurnal Teologi Gracia Deo, 2020)
Technological developments and changes in civilization in the era of globalization sweeping the world today has caused a multidimensional crisis so that the necessary mission service activities for outreach souls that need to be saved. Mission activities are the fulfillment of God's mission for the salvation of all humanity. The Holy Spirit must be present in every mission of mission, not just with funds and resources. This article discusses mission in a biblical perspective in the midst of a multidimensional crisis sweeping the world and its impacts with a qualitative descriptive method from literature study. The results and discussion show how important the role of mission is by involving church leaders who have a vision to mobilize local congregations involved in missionary activities for the salvation of God's people. Abstrak Perkembangan teknologi dan perubahan peradaban pada era globalisasi melanda dunia saat ini telah menimbulkan krisis multidimensi sehingga diperlukan kegiatan pelayanan misi untuk penjangkauan jiwa-jiwa yang perlu diselamatkan. Kegiatan misi merupakan penggenapan misi Allah bagi keselamatan seluruh umat manusia. Roh Kudus harus dihadirkan dalam setiap pengutusan kegiatan misi, bukan hanya sekedar dengan dana dan daya. Artikel ini membahas misi dalam perspektif alkitab di tengah krisis multidimensi yang melanda dunia serta dampak-dampaknya dengan metode deskriptif kualitatif dari kajian pustaka. Hasil dan pembahasan menunjukkan betapa pentingnya peranan misi dengan melibatkan pemimpin jemaat yang memiliki visi untuk memobilisasi jemaat lokal terlibat dalam kegiatan misi untuk keselamatan umat Tuhan.